2004
DOI: 10.1592/phco.24.5.500.33359
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Management and Control in Primary Care: A Study of 20 Practices in 14 States

Abstract: Study Objective. To describe the management and control of hypertension in primary care practice. Design. Retrospective medical record review. Setting. Twenty primary care practices in 14 states. Patients. Thirteen thousand forty-seven patients with hypertension. Measurements and Main Results. Diagnoses, drugs prescribed, and blood pressure readings were extracted from the electronic medical record at each practice in the study. For patients with hypertension and comorbid diagnoses, the most recent blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
54
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 23 publications
11
54
2
Order By: Relevance
“…11 However, among the hypertensives receiving treatment in general practice in Poland, the blood pressure control rate is lower than 10% according to the control level of 140/90 mm Hg. 12 Although varying figures are presented for the blood pressure control rate among hypertensive patients receiving treatment in primary care services in USA, [13][14] overall they are higher than those reported for European countries. Maue et al 13 have reported BP control rate according to the level of 140/90 mm Hg to be 41% (36% according to the 130/85 level for diabetics) in USA primary care services, compared with the approximate 50% reported by Ornstein et al…”
Section: Discussionmentioning
confidence: 99%
“…11 However, among the hypertensives receiving treatment in general practice in Poland, the blood pressure control rate is lower than 10% according to the control level of 140/90 mm Hg. 12 Although varying figures are presented for the blood pressure control rate among hypertensive patients receiving treatment in primary care services in USA, [13][14] overall they are higher than those reported for European countries. Maue et al 13 have reported BP control rate according to the level of 140/90 mm Hg to be 41% (36% according to the 130/85 level for diabetics) in USA primary care services, compared with the approximate 50% reported by Ornstein et al…”
Section: Discussionmentioning
confidence: 99%
“…6,7 However, studies evaluating data from those with hypertension-obtained from various sources such as national survey data, epidemiologic studies, ambulatory care practices, and high-risk patients-report a varying rate of hypertension control ranging from 29% to 50%. 4,[8][9][10][11][12][13][14][15][16][17] Medication nonadherence is cited as the primary cause for lack of hypertension control. 5,18 Medication nonadherence is defined as the failure to adhere to medication instructions, either willfully or inadvertently.…”
Section: Morisky Medication Adherence Scale (Mmas)mentioning
confidence: 99%
“…In NHANES and most epidemiological studies, the definition of hypertension is based on the blood pressure recorded at the study examination and the use of antihypertensive medications. Failure to account for use of nonpharmacological therapies may misclassify some individuals as nonhypertensive when they are in fact treated and controlled, 6,39 resulting in an underestimation of hypertension control rates. In contrast, several studies, including the NCQA report, rely on International Classification of Disease, ninth revision, diagnoses of hypertension or diagnoses contained in the medical record, 15,39 an approach that may inflate estimates of hypertension control for 2 reasons.…”
Section: Caveats To Be Considered When Interpreting Data On Hypertensmentioning
confidence: 99%